A Study of BYOD adoption from the lens of threat and coping appraisal of its security policy. Issue 6 (3rd July 2018) - Cho, Vincent; Ip, W.H.
ABSTRACT: Why would employees adopt bring your own device (BYOD)? Would employees feel risk-taking to perform their work by using their own devices? Would peer pressure and company policy help encourage their employees to BYOD and how? Using the Technology Threat Avoidance Theory (TTAT), we hypothesize the intention of adopting BYOD is due to the accessing of security policy by threat and coping appraisal. Moreover, we predict perceived usefulness, perceived ease of use, social influence, organizational commitment and job security are essential for formulating the adoption intention. In this study, 450 random employees were surveyed on their adoption perception of BYOD in their respective companies. The results support most of our hypotheses. We uncover perceived cost and privacy protection within the TTAT framework reflect no significance while organizational commitment and job security posit the strongest influences on employees' BYOD adoption intention. This finding suggested that in order to roll out a successful and sustainable adoption intention on BYOD, organizations must consider measurements to build up employees' job security as well as generate a strong sense of organization commitment. Specifically, our analyses show adoption intention is also affected by gender, age, and education level.